Experimental evaluation of steel fiber effect on mechanical properties of steel fiber-reinforced cement matrix (Fracture and Structural Integrity, 2017)
This paper investigates the possibility of combining steel fibers with different weight percentages along with their functions in increasing compressive strength, indirect tensile strength and bending strength. In this study, two types of steel fibers, hooked and crimped, have been employed in the preparation of samples. These fibers have a length to diameter ratio of 30 mm and 50 mm (L/D=30 and L/D=50). Further, the combination of these fibers caused a reduction in concrete flow and reduced its efficiency. The combination of these fibers caused considerable increase of concrete bending strength compared to fibreless and single-fiber type concretes. In this research, tensile strength and bending strength of samples with 1.5%, 2% and 2.5% fibers were investigated in which the tensile strength and bending strength of all samples increased. However, there were very considerable increases in tensile strength and bending strength of samples made with hybrid crimped fibers. The results indicated that steel fibers did not have much impact on concrete compressive strength.
Keywords: Mechanical properties; Fiber concrete; Hybrid concrete; Steel fibers; Indirect tensile test